Effect of multi-step and single- step dentin bonding agents on the bond strength of composite to dentin - Maleknejad F; Hoseini AA; Ghawamnasiri M; Salari T (Tehran University of Medical Sciences, 2002)
Composite resin restorative materials, that nowadays are used as tooth-colour materials, have both benefits and weaknesses. One of these weaknesses is the contraction resulted from resin polymerization which influences on the composite dentin bond strength and it has been tried to be eliminated by different bonding systems. The aim of this in-vitro study was to compare the dentin bond strength of two dentine adhesive systems: multi-step Scoth Bond Multipurpose (SBMP) and single- step Excite, by two composites of Ideal Makoo and Tetric. One hundred sixty (160) sound human molars were selected. At first they were debrided and mounted with acrylic resin in molds. The enamel of the buccal surface was eliminated by diamond burs. To provide a flat dentin surface, it was removed about lmm. Then, based on the type of dentin adhesive, they were divided into two groups of 30 teeth and were applied on the exposed dentine surface according to the manufacturer's instructions. Then, each group was divided into two subgroups of 15, based on the type of composite resin. Cylinders of the desired composite resin, attached to the dentin surface, were used for 80 seconds. The samples were stored in 100% humidity (37°c) for 24 hours. The bond strengths was measured by a cross head blade with the speed of 2mm/min. Variance analysis and Duncan test, with 95% confidence level, showed that statistically, two factors of adhesive and composite, interact on each other, in bond strength. There was no significant difference in bond strength, between two composites with similar adhesives, however, comparing two different adhesives with the same composite, showed that the bond strength of Tetric with Excite (28.39) was more than that of SBMP (17.98 Mpa). Finally, it was recognized that among four experimental groups, there was only a significant difference in bond strengths, between Tetric-Excite with Tetric- SBMP. This study shows that dentin bond strength is influenced by dentin bonding agents, composite type and dentin structure, and using a type of composite with a dentin bonding agent, manufactured by the same company, results in a higher bond strength.